Effect of the association of microparticles and nano-sized β-calcium glycerophosphate in conventional toothpaste on enamel remineralization: In situ study - Emerenciano, Nayara Gonçalves [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Gonçalves, Francyenne Maira Castro [UNESP]; Quinteiro, Julia Paião [UNESP]; de Camargo, Emerson Rodrigues; Silva-Sousa, Yara Teresinha Corrêa; Danelon, Marcelle [UNESP] (Elsevier, 2023)
Objectives: This in situ study aimed to assess the remineralizing effect of a fluoride toothpaste supplemented with β-calcium glycerophosphate in both micro (β-CaGPm) and nano-sized forms (β-CaGPn). Methods: This blind and cross-over study was performed in 4 phases, each spanning 3 days. Twelve volunteers utilized palatal appliances containing four bovine enamel blocks with artificial caries lesions. Volunteers were randomly assigned to the following treatment groups: Placebo (no F-β-CaGPm-β-CaGPn); 1100 ppm F alone (1100F); 1100F plus 0.5% micrometric β-CaGP (1100F-0.5%β-CaGPm); and 1100F plus 0.25%nano-sized β-CaGP (1100F-0.25%β-CaGPn). Participants were instructed to brush their natural teeth with the palatal appliances in the mouth for 1 min (3 times/day), ensuring that the enamel blocks were exposed to the natural toothpaste slurries. Following each phase, evaluations were conducted to determine the percentage of surface hardness recovery (%SHR), integrated recovery of subsurface hardness (ΔIHR), profile subsurface lesion through polarized light microscopy (PLM), as well as fluoride (F), calcium (Ca), and phosphorus (P) concentrations within the enamel. Data were analyzed by ANOVA and Student-Newman-Keuls test (p < 0.001). Results: Treatment with 1100F-0.25%β-CaGPn resulted in %SHR ∼69 % and ∼40 % higher when compared to 1100F and 1100F-0.5%β-CaGPm (p < 0.001). The reduction in lesion body (ΔIHR; PLM) was ∼40 % higher with 1100F-0.25%β-CaGPn (p < 0.001) compared to 1100F. The addition of β-CaGPm and β-CaGPn did not influence enamel F concentration (p > 0.001). Treatment with 1100F-0.25%β-CaGPn led to an increase in the concentration of Ca and P in the enamel (p < 0.001). Conclusion: The addition of 0.25%β-CaGPn into 1100F formulation increased the bioavailability of calcium and phosphate, promoting a higher remineralizing effect. Clinical significance: Toothpaste containing 1100F-0.25%β-CaGPn showed a potential of higher remineralization to 1100 ppm F and 1100 ppm F micrometric β-CaGP could be a strategy for patients at caries activity.
Keywords: Dental enamel; Fluoride; Phosphate; Remineralization